Effect of Corrosion on Wear Resistance of the Composite Based on GX120Mn13 Cast Steel Zonally Reinforced with Particles (Al2O3+ZrO2) - Medyński, Daniel (Archives of foundry engineering, 2023)
The subject of the work are modern composite materials with increased wear resistance intended for elements of machines operating in difficult conditions in the construction and mining industries. The study determined the effect of zone reinforcement of GX120Mn13 cast steel with macroparticles (Al 2O 3+ZrO 2) on the corrosion resistance and abrasion wear of the composite thus obtained. SEM studies have shown that at interface between two phases, and more precisely on the surface of particles (Al 2O 3+ZrO 2) a durable diffusion layers are formed. During the corrosion tests, no significant differences were found between the obtained parameters defining the corrosion processes of GX120Mn13 cast steel and GX120Mn13 with particles (Al 2O 3+ZrO 2) composite. No intergranular corrosion was observed in the matrix of the composite material, nor traces of pitting corrosion at both phases interface. This is very important in terms of tested material’s service life. Reinforcement of cast steel with particles (Al 2O 3+ZrO 2) resulted in a very significant improvement in the abrasion resistance of the composite – by about 70%. After corrosion tests, both materials were subjected to further operational investigations. These examinations consisted in determining the impact of corrosion processes on the durability of the composite in terms of abrasion. The obtained results indicate that corrosion processes did not significantly deteriorate the wear resistance of both the cast steel and the composite.